PENINGKATAN PRODUKTIVITAS MELALUI PERBAIKAN PROSES KERJA DENGAN GERAKAN LIMA LANGKAH (Dinamika Ekonomi, 2003)
A companv ma{ find the t.o}::JH;Ih. .t.*.nts carry out their functionsand responsibility as given before. As a consistent very staff should (seiri), carry out a saving (seiton), maintain self and environmenshtaolu lcdle wanolirnke sresg (usleairsloyand seiketsu) as well as being discipline is the key to achieve the goal of the company.